A MEETING WITH DIVERSITY IN ELEMENTARY SCHOOL EDUCATION THROUGH THE PROJECT SIMPLESMENTE DIFERENTE FROM THE PERSPECTIVE OF THE TEACHER, THE CHILD AND THE FAMILY - Araujo, Luciana Aparecida de [UNESP]; Cordeiro, Ana Paula [UNESP]; Mosca Giroto, Claudia Regina [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
From the perspective of inclusive education, Childhood Education must meet the specificities of the diversity of students, including the target audience of Special Education. Facing such commitment, this study aimed to investigate the conceptions about diversity among the children of a kindergarten class, their families and teacher, from the project Simplesmente Dfferente, elaborated and developed collaboratively through a work project. The analysis included thematic axes, among which we highlighted Conceptions about diversity in the context of the Childhood Education in the inclusive perspective, which indicated possibilities of re-signification on diversity, based on the methodology used, as well as the necessity, for the school to set this topic in its pedagogical practices.
Keywords: Diversity; Childhood education; Inclusive education; Special education